ANALISIS STABILITAS LERENG DAN ALTERNATIF PENANGANANNYA (STUDI KASUS LONGSORAN JALAN ALTERNATIF TAWANGMANGU STA 3+150 – STA 3+200, KARANGANYAR) - Rahmawan Bagus Pratama; Imam Muslih Muhibbi; Indrastono Dwi Atmanto; Siti Hardiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
This final project provides soil stability and the handling on alternative roads between Tawangmangu-Plaosan STA 3+150-STA 3+200, Karanganyar. The landscape in this area is rather steep and unstable, making the soil here has a high potential landslides. Based on the results of the drill testing which has done manually in this area, the soil contains gravelly-silt, sandly-silt and silt-stone. The analysis was done with Fellenius method and Plaxis v.8.2. Based on Fellenius method calculation, the safety factor value of the slope is 1,4701, while with Plaxis software, the safety factor value is 1,3476. Those values above are less than minimal safety requirement value of slope which is 1,5, so this landscape has a great potential of landslide. There are two alternative suggestions to handle this situation. The first one is adding 10 meters of Bored Piles into Counterfort wall. The other method is using 11 meters of Bored Piles. The choosen method for this project was using 11 meters of Bored piles. Bored Piles was choosen because it need lesser concrete volumes than Counterfort wall. Those bored piles has diameters of 0,8 meters. It was placed at the +1191,50 above the ground and 16 meters from the centerline. The results show that this alternative increase the value of safety factor up to 1,6383.